Performing Sacral Spaces – Spatializing Sacral Performance - Leonhard, Teresa (Review of ecumenical studies, 2021)
Spaces are closely connected with actions. By implementing an artistic-phenomenological approach, the existing interplay between sacral space and performance (highlighted bodily actions) can be found in the idea of cultural performance, which integrates the interdependance of movement and lively space, the origin of one in another. As space is something in motion, something that is created, in sacral spaces human beings experience an impact of space on the body and vice versa the effects of movement creating space. Performing "Artists in Church" encounter a space characterized by actions generating knowledge and "nally intermediate: the idea of transformation, geometry, places, absence, threshold and transcending. Performance Art provokes and leads syntopically and sympathetically to an aesthetic way of understanding space and action.